(untitled) - Semer, Nadine B (Philadelphia, 2001)
Hanley & Belfus) Univ. of Southern California, Los Angeles. Manual of tips and techniques for professionals without advanced surgical training. Includes an easy-to-read format, step-by-step procedures, line drawings and photographs, and illustrative cases. Softcover. DNLM: Reconstructive Surgical Procedures.
Keywords: Surgery, Plastic,Rural health services